2018
DOI: 10.1111/acel.12774
|View full text |Cite
|
Sign up to set email alerts
|

Antagonizing peroxisome proliferator‐activated receptor γ facilitates M1‐to‐M2 shift of microglia by enhancing autophagy via the LKB1–AMPK signaling pathway

Abstract: SummaryMicroglia‐mediated neuroinflammation plays a dual role in various brain diseases due to distinct microglial phenotypes, including deleterious M1 and neuroprotective M2. There is growing evidence that the peroxisome proliferator‐activated receptor γ (PPARγ) agonist rosiglitazone prevents lipopolysaccharide (LPS)‐induced microglial activation. Here, we observed that antagonizing PPARγ promoted LPS‐stimulated changes in polarization from the M1 to the M2 phenotype in primary microglia. PPARγ antagonist T00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
111
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(124 citation statements)
references
References 42 publications
(47 reference statements)
3
111
0
1
Order By: Relevance
“…To our surprise, rosiglitazone also inhibited proinflammatory microglial polarization, during which the expression of CD206 and Arg-1 is increased. 32 In addition, we observed the loss of neurons in temporal lobe and hippocampal tissues after SE, consistent with the previous study. 48 After rosiglitazone administration, the number of NeuN+ cells was increased 3 days after SE, especially in CA3 hippocampi.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…To our surprise, rosiglitazone also inhibited proinflammatory microglial polarization, during which the expression of CD206 and Arg-1 is increased. 32 In addition, we observed the loss of neurons in temporal lobe and hippocampal tissues after SE, consistent with the previous study. 48 After rosiglitazone administration, the number of NeuN+ cells was increased 3 days after SE, especially in CA3 hippocampi.…”
Section: Discussionsupporting
confidence: 92%
“…Our study revealed that the PPARγ agonist rosiglitazone can suppress the activation of microglia by flow cytometry and immunofluorescence staining for Iba‐1. To our surprise, rosiglitazone also inhibited proinflammatory microglial polarization, during which the expression of CD206 and Arg‐1 is increased . In addition, we observed the loss of neurons in temporal lobe and hippocampal tissues after SE, consistent with the previous study .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Norbixin by suppressing A2E-induced PPAR-a transactivation may thus release A2E inhibitory effect through PPAR-a resulting in increased CCL2 production. However, antagonizing PPARg also reduces CCL-2 expression during microglia differentiation in vitro (45). Altogether, these conflicting observations suggest that, upon A2E treatment, CCL2 overexpression may result from a subtle equilibrium between RARs, PPAR-a and -g transactivation levels.…”
Section: Discussionmentioning
confidence: 96%